Spatial control of nucleoporin condensation by fragile X‐related proteins. (24th July 2020) - Agote‐Aran, Arantxa; Schmucker, Stephane; Jerabkova, Katerina; Jmel Boyer, Inès; Berto, Alessandro; Pacini, Laura; Ronchi, Paolo; Kleiss, Charlotte; Guerard, Laurent; Schwab, Yannick; Moine, Hervé; Mandel, Jean‐Louis; et al.
Abstract: Nucleoporins (Nups) build highly organized nuclear pore complexes (NPCs) at the nuclear envelope (NE). Several Nups assemble into a sieve‐like hydrogel within the central channel of the NPCs. In the cytoplasm, the soluble Nups exist, but how their assembly is restricted to the NE is currently unknown. Here, we show that fragile X‐related protein 1 (FXR1) can interact with several Nups and facilitate their localization to the NE during interphase through a microtubule‐dependent mechanism. Downregulation of FXR1 or closely related orthologs FXR2 and fragile X mental retardation protein (FMRP) leads to the accumulation of cytoplasmic Nup condensates. Likewise, models of fragile X syndrome (FXS), characterized by a loss of FMRP, accumulate Nup granules. The Nup granule‐containing cells show defects in protein export, nuclear morphology and cell cycle progression. Our results reveal an unexpected role for the FXR protein family in the spatial regulation of nucleoporin condensation. Synopsis: Fragile X‐related proteins and dynein inhibit ectopic phase separation of nucleoporins in the cytoplasm and facilitate their localization to the nuclear envelope during G1 phase of the cell cycle. Fragile X‐related (FXR) proteins and dynein regulate localization of cytoplasmic nucleoporins. FXR‐Dynein pathway downregulation induces aberrant cytoplasmic condensation of nucleoporins. Cellular models of Fragile X syndrome accumulate aberrant cytoplasmic nucleoporin condensates. FXR‐Dynein pathway regulates nuclear morphology and cell cycle progression. Abstract : Fragile X‐related proteins and dynein inhibit ectopic phase separation of nucleoporins in the cytoplasm and facilitate their localization to the nuclear envelope during G1 phase of the cell cycle.